RETRACTED: Granulometric composition and moisture capacity of the soil in old-age apple orchards of the Lipetsk region - Zakharov Vyacheslav; Gulidova Valentina; Kravchenko Vladimir; Sotnikov Boris (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001